Utilization of Graphite Nanoparticles as a Hybrid Hole Transport Layer in Non-Fullerene Organic Solar Cells - Magaly Ramirez-Como; Monica M. Valdez-Mata; Angel Sacramento; Jose L. Casas-Espinola; Luis Resendiz; Lluis F. Marsal (IEEE Journal of the Electron Devices Society)
This study investigates the impact of incorporating graphite nanoparticles (GNPs) into poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) as hybrid hole transport layer (HTL) in non-fullerene organic solar cells (NF-OSCs) based on PBDB-T-2F:BTP-4CL. The concentration of GNPs in the PEDOT:PSS layer was varied to investigate their impact on the overall device behavior. The PCE initially increased with the GNPs concentration up to 5% v/v, reaching a maximum enhancement of 6.43%, which was attributed to the increased JSC. Current-voltage measurements and Mott-Schottky analysis through capacitance-voltage characteristics were conducted to evaluate the behavior of the charge recombination and built-in potential due to the concentration variation of the GNPs into PEDOT:PSS. This study illustrates the potential of GNPs to improve OSC performance through enhanced light absorption, reduced recombination losses, and improved charge carrier transport, indicating promising prospects for GNPs on interface layers in OSCs.